Multivariate near infrared spectroscopy models to monitor polycondensation production process reactions. (May 2015) - Mota, Helena I.; Correia, Maria Joana Neiva; Bordado, João C.M.
Graphical abstract: Highlights: NIR spectroscopy was applied in-line to monitor the polyesterification reaction. The different steps of the polyesterification process were distinguished by PCA. PLS models were developed to predict the acid value and the AMW. The models presented good accuracy with an acceptable RMSEP. NIRS with chemometrics is a suitable alternative to usual analytical methods. Abstract: The control of polycondensation progress in the reactor is usually carried out by the determination of the acid value and the Average Molecular Weight (AMW) using analytical methods that are expensive and time consuming. Alternatively, this work reports the use of near infrared spectroscopy (NIRS), coupled with multivariate calibration techniques, to determine these two parameters. Thus, polycondensations of Adipic Acid with 1, 6-Hexanediol were carried out at 130 °C and followed in-line using NIRS. Principal Component Analysis (PCA) was used to perform the qualitative analysis of the spectra, whereas Partial Least Squares (PLS) regression was used to develop calibration models between the spectra and the acid value and the average molecular weight of the polymers. The results support that NIRS, in combination with multivariate calibration, is a promising and an accurate method for monitoring the polycondensation process.